Forming relationships on the e-commerce market as a basis to build loyalty and create value for the customer. Empirical findings = Kształtowanie relacji na rynku e-commerce jako podstawa budowania lojalności i tworzenia wartości dla klienta. Analiza empiryczna - Michałowska, Mariola; Kotylak, Sławomir; Danielak, Wiesław (Zielona Góra: Faculty of Economics and Management Press)
The dynamic development of information technology, especially the Internet, which has taken place in recent years has brought many new opportunities to use the Internet in businessoperations. The Internet has created new opportunities for the development of enterprises. It was its dynamic boom that enabled e-commerce to gain in importance, and along with it made the changes in consumer behavior in terms of place, time and purchasing conditions.
Keywords: relacje; lojalność; tworzenie wartości; klient; sklepy internetowe; relationships; lovalty; value creation; e-comerce; customer; Internet shopping